Zero Distance Management in the Quantum Age - Zohar, Danah (Springer Nature, 2022)
This open access book offers a new management meta-theory to replace Taylorism. It presents a new paradigm in management thinking and a new, practical organizational model for implementing it in our personal and working lives, in our companies, in our communities and nations, and in a sustainable global order. It will offer an understanding of why and how "thinking-as-usual" is failing both business and political leaders in these new times, and it will advocate new thinking and new management practices that are so radically new that they turn everything we have taken for granted inside out and upside down. This new management model is called "Quantum Management Theory", because it is rooted in the new paradigm bequeathed to us by quantum physics and its younger sibling, complexity science.